Nonclinical Similarity of the Biosimilar Candidate ABP 938 with Aflibercept Reference Product - Neungseon Seo; Scott Kuhns; Dina A. Andrews; Alexander Colbert; Vincent Chow; Jennifer Liu (Ophthalmology and Therapy)
Abstract Introduction ABP 938 is being developed as a biosimilar to Eylea® (aflibercept reference product [RP]), an anti-vascular endothelial growth factor (VEGF) drug used in the management of retinal diseases. Previously, a comparative analytical similarity assessment demonstrated that ABP 938 and aflibercept RP have the same amino acid sequence and exhibit similar higher-order structure and biological activity. The nonclinical studies described here were designed to assess the in vitro pharmacology and the in vivo pharmacokinetics (PK), toxicokinetics (TK), and safety profiles of ABP 938 compared to aflibercept RP. Methods In vitro target-binding kinetics and affinity for VEGF-A and placental growth factor (PIGF) isoforms were evaluated using surface plasmon resonance (SPR). Effector functions were assessed by cell-based assays. PK was evaluated in a nonterminal intravitreal (IVT) ocular distribution study in rabbits. Safety was assessed in a 1-month IVT study in cynomolgus monkeys. Results SPR results demonstrated that ABP 938 is similar to aflibercept RP in binding kinetics and affinity for VEGF-A111, VEGF-A121, VEGF-A165, VEGF-A189, PlGF-1, and PlGF-2 isoforms. No antibody-dependent cellular cytotoxicity, antibody-dependent cellular phagocytosis, or complement-dependent cytotoxicity was observed with ABP 938 and aflibercept RP. Results from the nonterminal ocular distribution study in rabbits indicated that there were no meaningful differences in the distribution kinetics between intravitreally injected ABP 938 and aflibercept RP. Additionally, there was no evidence of ocular or systemic toxicity associated with IVT administration of ABP 938 in a repeat-dose, 1-month toxicology study in cynomolgus monkeys; toxicokinetic and toxicology profiles were similar to aflibercept RP. Conclusions This integrated assessment of results from the in vitro pharmacology assessment and in vivo PK and TK/toxicology profiles formed the nonclinical portion of the totality of evidence demonstrating ABP 938 is a biosimilar to aflibercept RP.